Analisis Sharia Compliance Pada Mekanisme Produk Kafalah Pembiayaan Surety Bond PT. Penjaminan Jamkrindo Syariah Cabang Medan - Yusuf, M.; Lubis, Fauzi Arif (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2024)
The purpose of this study was to find out the mechanism of the Surety Bond financing kafalah product at PT Penjaminan Jamkrindo Syariah Medan Branch and to find out the sharia compliance analysis in the Surety Bond financing process and the suitability of its application in terms of sharia compliance dimensions and provisions. This research departs from the framework of thinking, namely the application of shariah compliance to the surety bond financing mechanism, where shariah compliance is the basic thing that distinguishes between shariah financing and conventional financing. If a sharia financing has followed sharia compliance by implementing all fatwas that regulate the financing of a product, then the application of sharia compliance is correct. As stipulated in the DSN Fatwa No.4/DSN-MUI/IV/20. regulates the ownership of goods in Surety Bond financing transactions. The research method used in this research is descriptive method. With primary data sources taken from the research location of PT Penjaminan Jamkrindo Syariah Medan Branch, namely regarding Shariah compliance in the mechanism of the Surety Bond financing kafalah product. While the secondary data sources used in this study came from books, articles, the internet, and other sources. Keywords : Sharia Compliance, Jamkrindo syariah, produk surety bond.